2008
DOI: 10.1152/japplphysiol.01346.2007
|View full text |Cite
|
Sign up to set email alerts
|

Resistance training and timed essential amino acids protect against the loss of muscle mass and strength during 28 days of bed rest and energy deficit

Abstract: Spaceflight and bed rest (BR) result in losses of muscle mass and strength. Resistance training (RT) and amino acid (AA) supplementation are potential countermeasures to minimize these losses. However, it is unknown if timing of supplementation with exercise can optimize benefits, particularly with energy deficit. We examined the effect of these countermeasures on body composition, strength, and insulin levels in 31 men (ages 31-55 yr) during BR (28 days) followed by active recovery (14 days). Subjects were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 33 publications
8
83
0
Order By: Relevance
“…Given the synergistic effects of exercise training and increased protein intake, it is disappointing that an 'exercise þ leucine' group was not included in this study. However, in a 28 d bed rest study, Brooks et al [46], observed no additional effect of a 15 g EAA þ 30 g sucrose supplement taken once per day when combined with exercise compared to exercise alone [46].…”
Section: Immobilization and Bed Restmentioning
confidence: 98%
“…Given the synergistic effects of exercise training and increased protein intake, it is disappointing that an 'exercise þ leucine' group was not included in this study. However, in a 28 d bed rest study, Brooks et al [46], observed no additional effect of a 15 g EAA þ 30 g sucrose supplement taken once per day when combined with exercise compared to exercise alone [46].…”
Section: Immobilization and Bed Restmentioning
confidence: 98%
“…More recently, Brooks conducted a 28-day bed rest during which they investigated the effect of a supplementation in essential amino acids during three similar bed rests (Brooks et al, 2008). The first group underwent strict bed rest with amino acid supplementation.…”
Section: Studies Showing No Significant Benefitsmentioning
confidence: 99%
“…The loss of lower body strength was −22.4 ± 5.8 lbs in the dietary supplemented group whereas it decreased by −8.0 ±11.3 and −6.0 ± 6.1 lbs in the resistance exercise and combined treatment groups. Brooks concluded that "the combination of resistance exercise and essential amino acid supplementation conferred greater protection against the reductions in mass and strength than an amino acid supplement alone" (Brooks et al, 2008). The resistance exercise alone protocol conferred the same magnitude of protection as did the combined treatment of resistance exercise plus amino acid supplementation.…”
Section: Studies Showing No Significant Benefitsmentioning
confidence: 99%
“…The loss of skeletal muscle mass observed during a period of bed rest (23,44,62) or lower limb immobilization (16,26,28,30) has been attributed primarily to a reduction in basal and/or postprandial muscle protein synthesis rates. Maintaining some level of physical activity during a period of disuse is required to attenuate the decline in muscle protein synthesis rates and prevent excessive muscle tissue loss (2,12,24,47,52,64). However, under many clinical conditions (e.g., hospitalization due to illness or injury), maintenance of physical activity is often not practical or even feasible.…”
mentioning
confidence: 99%